The Soviet Occupation of Afghanistan - Mushtaqur Rahman (International Institute of Islamic Thought, 1986)
ISLAM is as natural to the people of Afghanistan as the air they breathe. Any system repugnant to Islam or the introduction of alien forces to introduce a new social order has always been resisted by the Afghans. The present Afghan-Soviet war is one such story. The war is a matter of vital importance because its outcome will immensely affect Pakistan, Iran, and the rest of the Muslim world. It will also upset the balance of power between the West and the Soviets, and might change the direction of oil flow. It is curious that the war is not given the support or attention it deserves, in spite of its global ramifications. The West perhaps ignores the war as Afghanistan is far removed from the Western mainstream, and its impact is not generally understood because the Afghan Mujahideen lack a sophisticated network of information. Moreover, the Soviets continue misleading the world by claiming the war is only a law and order problem between the Afghan government and a handful of “bandits” encouraged from outside. The war is neither a law and order matter nor its impact hard to realize. Afghan Mujahideen are fighting the Soviets to force them out of Afghanistan, and the Soviets are trying to hold on using biological, chemical, and other sophisticated weapons. In spite of enormous destruction and genocide, the Afghan Mujahideen are determined to fight to the last, and so apparently are the Soviets to consolidate their occupation of Afghanistan. This paper presents an analysis of the war and its impact on Pakistan, the Muslim world, and the West from a geopolitical standpoint. A brief discussion of Afghanistan explains the former status of Afghanistan as a buffer state first between the Russians and the British and later between the Soviets and Pakistan. Modern Afghanistan dates back to 1747 when Ahmad Shah Durrani took over reins of that country. More or less during the same time, the British ...